Nacionalinis tapatumas ir globalizacija. Irano Islamabado ir Gilanegarbo miestų pagrindinių studijų studentų apklausa - Javadi, Alimohammad; Javadi, Maryam (Information & Media, 2008)
Pastaraisiais metais plėtojantis modernizmui ir modernizacijai pastebima pasaulinių nacionalinio tapatumo pokyčių, kurie skatina nacionalizmo ir tapatybės tyrimus. Komunikacinės technologijos ir globalizacijos procesas gali turėti įtakos nacionaliniam tapatumui. Pagrindinis šio pranešimo tikslas – aprašyti ir ištirti tautinį tapatumą ir esminius su juo susijusius veiksnius. Šiam tikslui atskleisti taikomas tiriamasis apžvalgos metodas, pasirinkta apklausti Islamabado ir Gilanegharbo 165 studentus bakalaurus. Tyrimo rezultatai parodė, kad nacionalinis tapatumas yra labai svarbus (jis vertinamas 3,92 skalėje nuo 0 iki 5), taip pat kaip svarbūs įvardijami ir kiti kintamieji, tokie kaip interneto aplinka, palydovinių ir palydoviniu būdu perduodamų programų žiūrėjimas, vaizdo filmų ir televizijos programų žiūrėjimas. Nustatyta, kad šie veiksniai turi neigiamą įtaką nacionaliniam tapatumui.Analizuojant kurdų pasisakymus matyti, kad nedidelė populiacija, etninės ypatybės, tradicijos kartais nulemia nacionalinio tapatumo silpnėjimą.National identity and globalization. A survey among undergraduate students in Islamabad and Gilanegharb cities (Iran)Alimohammad Javadi, Maryam JavadiSummaryIn the recent years, due to the expansion of modernism and modernization on a global scale, there have been developments at cultural and structural levels, resulting in a change in national identity and making the study of nationalism and identity become an important topic in social science. Communication technologies and globalization can affect national identity. The main goal of this article is to describe and analyse national identity and related major factors. For this purpose, a survey of a sample of 165 undergraduate students in the cities of Islamabad and Gilanegharb (Iran) in the education year 2007 was considered, (the population are Kurds in Islamabad and Gilanegharb, Kurds being an ethnicity in Iran). The results have indicated that the rate of national identity is high (mean = 3.92 of 0 to 5), and the variables at the use of sexual environment of the Internet, the rate of using satellite programs and their kinds, VCD and related programs have a negative effect on national identity, and the variables like satisfaction with work and facilities of welfare, intimacy with family, satisfaction with having facilities of welfare in the nation of Kurds have a positive effect on national identity. Ethnicity and the low size of population affect the decrease of national identity. In the multi-variable regression analysis, the effect of independent variables reached about 64%, and the variables that could be included as independent variables into the regression model are as follows: satisfaction with job in Iran, relationships with friends, ethnic intimacy with the family, the rate of the use of satellite, tradition and satisfaction with the facility of education.Key words: national identity, globalization, mass media, new media, ethnicitybsp;